Semantic and Lexical Changes in Neo-Latin Vocabulary in the Field of Medical Devices and Procedure - Krukowska, Sylwia (Collectanea Philologica, 2023)
The article concerns the possibility of using Latin as a means of communication by the medical community. It is an analysis leading to an answer to the question of the possibility of conveying in Latin the content, which determines the intellectual activity of a modern man. Meeting this challenge requires the introduction of new terms and phrases into Latin vocabulary. The currently used words in the ﬁeld of medical devices and procedures will be discussed. Motivation of Neo-Latin terms, the reasons for the word transformation and the directions of these changes, as well as calques from modern languages and the issue of terms that can be called ‚loan words returning’ (i.e. words of Latin origin, which survived in modern languages and returned to the Neo-Latin vocabulary, following the path: Latin to modern languages to Latin) will be the subject of the analysis. Finally, it will be focused on the intelligibility and communicativeness of these terms. The purpose of the study was to draw attention to the enormous potential of Latin and to demonstrate that Latin (similarly to modern languages) has the opportunity to meet the challenges posed by signiﬁcant technological progress and related to its requirement of creating new specialized terms.